Urgensi Perundang – Undangan Internasional Hague / Hague-Visby / Hamburg / Rotterdam oleh Indonesia - Zefanya, Anastasia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Many things are still being debated to ratify the law on the transportation of goods by sea in Indonesia. International legislation is like the international agreement Hague / Hague-Visby / Hamburg / Rotterdam. These four conventions have been mostly implemented by most of the world’s maritime countries, leaving several countries to defend their versions, including Indonesia. Indonesia still adheres to the 1898 code inherited from the Dutch colonial era. The comparative analysis resulted in similar implementations of versions of the four UNCITRAL conventions adopted by many countries. This strongly prompted Indonesia to replace the 1898 commercial code with the current international practice that conveys Indonesia’s best interests